Persepsi Siswa Laki-Laki Terhadap Pembelajaran Seni Budaya (Seni Tari) Di SMP Negeri 6 Pariaman - Regina Lausandry; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2021)
This research aims to look at and describe the perception of male students towards dance learning at SMP Negeri 6 Pariaman. This type of research is qualitative research using descriptive methods. The main instruments of this study are the researchers themselves and assisted with supporting instruments such as stationery and cameras. The data type uses primary and secondary data. Data collection techniques are carried out by observation, interview and library study. The steps of analyzing data are data collection, describing data and concluding data. The results showed that in general the perception of students on less well. This can be seen from the evaluation indicators in dance art learning at SMPN 6 Pariaman in grades VII and VII 3. Based on observations and interviews there are still many things that should be improved by the school in order to improve the learning outcomes of students some of them are as follows: (1) the view of male students towards the practice of dance art is less good according to them dance activities are activities carried out by female students, they prefer cultural arts lessons in theory of music art and fine arts karen is more suitable for men , male students feel ashamed to move their bodies because shame is ridiculed by friends (2) the teacher's educational background is very influential in achieving learning goals, the monotonous way of teaching teachers makes students lack excited, bored teachers should vary the way teaching should teach according to KD.